Nonlinear Fiber Optics - Agrawal, G. P. 1951- (Academic Press, 2019)
Nonlinear Fiber Optics, Sixth Edition, provides an up-to-date accounting of the nonlinear phenomena occurring inside optical fibers in telecommunications infrastructure and in the medical field. This new edition includes a general update to reflect the most recent research, extensive updates to chapter 13 on Supercontinuum Generation that reflect the use of chalcogenide fibers that extend Supercontinuum into the mid-infrared region, and a new chapter devoted to the nonlinear optics of multimode and multicore fibers. This book is ideal for researchers and graduate students in photonics, optical engineering and communication engineering.